Catalytic Synthesis of Pyrano- and Furoquinolines Using Nano Silica Chromic Acid at Room Temperature. (17th June 2013) - Gharib, Ali; Jahangir, Manouchehr
Abstract : Nano silica chromic acid (nano-SCA) is found to catalyze efficiently the three component-coupling reactions of aldehydes, amines, and cyclic enol ethers such as 3, 4-dihydro-2 H -pyran and 2, 3-dihydrofuran under mild conditions to afford the corresponding pyrano- and furanoquinolines in excellent yields with high endoselectivity. Interestingly, 2, 3-dihydrofuran afforded selectively endoproducts under the similar reaction conditions. Heterogeneous reaction conditions, easy procedure, short reaction time, and high yields are some important advantages of this method.